Dr. Žun ob začetkih sociologije prava na Slovenskem - Igličar, Albin (Pravnik, 2014)
Sociology of law was originating simultaneously with the origination of general sociology in the middle of the 19th century and remained in its frame. It was separated from the general sociology and became an independent scientific discipline only later. When the general sociology was already established and got the status of an academic discipline. i.e. at the beginning of the 20th century. Sociology of law in Slovenia must proceed from the cognitions of general sociological theory and use sociological methods in interpreting law as a social phenomenon. Dr. Žun's view was, that only with such a broad approach it is possible to explain social, interest, political, cultural, and economic circumstances, due to which some social relations are regulated by legal norms, to find conformity of real relations with ideal norms, to get to know the contents of legal culture in a global society.
Keywords: država; law; ocene in poročila; politics; politika; pravo; sociologija; sociologija politike; sociologija prava; sociology; state; Žun, Anton: Sociologija prava, sociologija, politična sociologija